E-066 Pathogenesis of Dural Sinus Malformations as Demonstrated by Fetal Imaging: A Decision-Making Crucible for Parents and Clinicians. (26th July 2014) - Orbach, D; Storey, A; Morash, D; Estroff, J; Smith, E; Trenor, C; Olson, H
Abstract : Introduction: Two recent concurrent and contrasting cases of dural sinus malformation (DSM), followed at serial time points in utero by ultrasound and MR at the Boston Children's Hospital Advanced Fetal Care Center (AFCC), illuminate the range of complex decision-making challenges faced by parents and consulting clinicians, and led us to study all such cases presenting to our institution over the past five years. Materials and methods: We reviewed serial imaging (MR and US) findings, including calibre and contents of the dural sac, presence or absence of feeding arteries, brain parenchymal signal, and ventricular and extraaxial spaces, as well as clinical outcome, for all 9 cases of DSM referred to the Boston Children's AFCC over the past five years. All cases of vein of Galen malformation, pial arteriovenous fistula, fetal pial vein thrombosis without sinus dilatation, and other pathologies were excluded. We additionally reviewed other published cases. Results: One of the two index cases showed no visible arterial inflow, an enlarged superior sagittal sinus (SSS)/torcular complex containing a small core of solid thrombus surrounded by stagnant blood, and a clear change in the dynamics of growth of the DSM, with development of a small focal brain parenchymal abnormality. The second case may represent the first middle meningeal arteries-to-SSS dural AVF visualised in detail in utero, and is contrasted with a morphologically homologous case of DSM diagnosed with acute neurologic presentation at age 6 months, and managed with endovascular intervention. Review of the 9 cases of in utero DSM consultations tracked by fetal ultrasound and MR at the AFCC over the past 5 years, and a review of other published cases, allowed us to develop a model of the pathogenesis of DSM. Prognosis seems to depend on the relationship of the gestational age to the particular temporal dynamics of the individual lesion. Conclusion: DSM may be diagnosed in utero at various stages of its pathogenesis – with a patent arteriovenous flow, or with a growing stagnant venous pouch. Detailed serial imaging demonstrates that differing temporal dynamics across cases may determine the natural history. Given the wide range of potential neurological outcomes, from normal development to severe disability, decision making in this context is often fraught with tension. Construction of rational individual management schema depends upon detailed assessment of each case. Disclosures: D. Orbach: None. A. Storey: None. D. Morash: None. J. Estroff: None. E. Smith: None. C. Trenor: None. H. Olson: None.